Evaluation of wheat cultivars in different sowing dates - Moreira, João Carlos Soares; Ignaczak, João Carlos (Pesquisa Agropecuaria Brasileira, 2014)
The Southern Brazilian Wheat Research Board reports every year a list of cultivars recommended for each wheat (Triticum aestivum L.) growing area of Rio Grande do Sul state along with the sowing date intervals in each region. In order to establish the best sowing date within the recommended period, a variance analysis on yield response was carried out in a group of 27 cultivars in the period of trial conducted in three different dates at Passo Fundo, RS, Brazil, during the years of 1983, 1984 and 1985. The results showed that the influence of year, sowing date, cultivar, as well as the interaction effects of year x sowing date, year x cultivar, sowing date x cultivar, and year x sowing date x cultivar were highly significant. It was not possible to determine for all cultivars the best sowing date for this region. Nevertheless, it was observed that the second sowing date showed to be more suitable for most of the cultivars.